Preferential flow in the understory soil of Hippophae rhamnoides at different stump heights - Liu, Lu; Liu, Xiaoyu; Yao, Yunfeng; Qi, Wei; Guo, Yuefeng (Frontiers in Environmental Science, 2023)
This study aimed to clarify the effects of stumping on preferential flow in the understory soils of Hippophae rhamnoides and to assess appropriate stumping height for optimization of preferential flow. Root properties, soil properties, and preferential flow for different H. rhamnoides stump heights (0, 10, 15, 20 cm, and no-stumping, labeled conditions S1, S2, S3, S4, and CK, respectively) were studied using in situ dye-tracing and laboratory analysis. The results showed that stumping significantly increased preferential flow development. This effect was maximized in condition S3, with dye-tracing coverage (DC) of 36.77%, maximum dye depth (MaxD) of 40.02 cm, uniform infiltration depth (Unifr) of 14.28 cm, preferential flow ratio (PFfr) of 23.85%, and length index (LI) of 96.72%. In terms of root length density (RLD), root mass density (RMD), root surface area density (RSAD), soil water content (SWC), soil total porosity (TP), mean weight diameter (MWD), and soil organic matter (SOM), the conditions were ranked S3>S2>S1>S3>CK; for root average diameter (RAD), they were ranked S3<S2<S1<S4<CK. Structural equation modeling showed that DC was affected directly by TP, MWD, and SWC and indirectly by RAD, RLD, RMD, RSAD, and SOM, explaining up to 89.1% of the variance. Thus, stumping of H. rhamnoides affected soil properties through the mechanism of root development, thereby improving preferential flow development in the soil and soil infiltration. The optimal stump height was 15 cm. These findings are critical for vegetation recovery and for prevention and control of soil erosion in feldspathic sandstone areas.